Joan as Jesus: A Feminist Theological Analysis of Dreyer's The Passion of Joan of Arc. Issue 4 (December 2016) - Guðmundsdóttir, Arnfríður
Abstract: The aim of this article is to explore Carl Theodor Dreyer's portrayal of Joan of Arc in his film The Passion of Joan of Arc (1928) as a female Christ‐figure. At the same time I argue that the film can serve as an important dialogue partner in ongoing christological discourse. The conclusion is that Dreyer's Joan provides a vivid image of Jesus Christ that challenges our fixation on Jesus' maleness, and helps us to understand better what we really mean when we claim that God, dressed in flesh, became human, like us, female or male.